Development Of Alumni Portal Application Based Android - Samsudin, Samsudin; Lubis, Riri Syafitri (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Alumni are graduates from a school, academy, high school, college, or university. Alumni are one of the important assets that must be embraced, coordinated, and developed as early as possible. The existence of alumni is very influential in improving the quality of an institution. So far, the Information Systems Study Program of UIN North Sumatra has not provided a means that can be used to collect data and track tracer study alumni so that the Information System of UIN North Sumatra has difficulties and obstacles in collecting and tracking data. tracer study alumni. The purpose of this research is to build an android-based application that can be used by alumni in filling out tracer study data online and can also assist the study program in tracking tracer study alumni easily and quickly through an android smartphone. The application development method used in this study is the Extreme Programming (XP) method which consists of planning, design, coding, and testing stages. In making a visual design of the application to be built, the author uses UML (Unified Modeling Language) tools consisting of use case diagrams, sequence diagrams, activity diagrams, and class diagrams. The application is built using the Kodular framework and the Airtable database. With this application, it is hoped that it will make it easier for alumni to fill in data and help the information system study program track alumni data easily and quickly through an Android smartphone.